(untitled) (Journal of Health Sciences, 2021)
Introduction: The assessment of the health-care system by its beneficiaries is based on evaluation of the public perception in regards to the performance of healthcare workers, the functioning of the health system, the effectiveness of health policy measures, and a number of other components. The aim of this study was to determine patients’ trust in the work of physiotherapists and the health-care system; determine the quality of communication between the patient and the physiotherapist and determine the quality of cooperation between healthcare workers in the provision of health services.Methods: The study is descriptive, conducted in five cities: Banja Luka, Bihać, Herceg Novi, Nikšić, and Podujevo. The confidence in health-care questionnaire developed by Calnan and Sanford (2004) was used as a research instrument, containing six areas of research: Attitude toward the patient, Health policy and patient care, Professionalism and expertise, Quality of health care, Communication and information, and Quality of cooperation.Results: The mean age of the subjects was 41 years, 24 females and 26 males. Subjects expressed the greatest satisfaction on subscales I - Attitude toward the patient (27.44 ± 3.59 out of 30) and IV - Quality of health care (36.60 ± 4.19 out of 40), which represents 91.5% of the possible maximum. This is followed by subscale V - Communication and information (20.8 ± 3.17 out of 25) corresponding to 83.2% of the possible maximum, followed by subscale III - Professionalism and expertise (15.68 ± 3.29 out of 20) which represents 78.4% of the possible maximum. Subjects showed the least satisfaction on subscales II - Health policy and patient care (16.94 ± 5.56 out of 25), which represents 67.8% of the possible maximum, and subscales VI - Quality of cooperation (9.94 ± 0.42 out of 15) which corresponds to 66.3% of the possible maximum.Conclusions: The research showed a high degree of satisfaction of subjects in various fields, which indicates a high degree of confidence in the work of physiotherapists and the health-care system. Research on a larger sample in needed for creation and implementation of the guidelines in the strategic documents of the countries in the region and for improvement of health policies and patient care.